2018
DOI: 10.1136/jim-2017-000518
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Plays a Crucial Role in the Mortality of Critically Ill Patients with Acute Renal Failure

Abstract: We aimed to clarify associations between nutritional status and mortality in patients with acute renal failure. De-identified data were obtained from the Medical Information Mart for Intensive Care III database comprising more than 40,000 critical care patients treated at Beth Israel Deaconess Medical Centerbetween 2001 and 2012. Weight loss and body mass index criteria were used to define malnutrition. Data of 193 critically ill patients with acute renal failure were analyzed, including demographics, nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…13 Nevertheless, patients with a BMI of ≥31 kg/m 2 had higher mortality, which was the same as those patients with a low BW (BMI <18 kg/m 2 ). 15,16 For the elderly (aged more than 65 years), a multicenter retrospective analysis that included 2015 patients with AKI which occurred in ICUs after major surgery revealed that patients with a BMI of 21–31 kg/m 2 had lower in-hospital mortality. 15 Results of the forest plot demonstrated that AKI patients who have a lower BMI levels (<18.5 kg/m 2 ) have a higher mortality risk than those with higher BMI (≥18.5 kg/m2) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Nevertheless, patients with a BMI of ≥31 kg/m 2 had higher mortality, which was the same as those patients with a low BW (BMI <18 kg/m 2 ). 15,16 For the elderly (aged more than 65 years), a multicenter retrospective analysis that included 2015 patients with AKI which occurred in ICUs after major surgery revealed that patients with a BMI of 21–31 kg/m 2 had lower in-hospital mortality. 15 Results of the forest plot demonstrated that AKI patients who have a lower BMI levels (<18.5 kg/m 2 ) have a higher mortality risk than those with higher BMI (≥18.5 kg/m2) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There was a U-shaped association of BMI with hospital mortality in elderly AKI patients. Zhang et al 16 Retrospective study. 193 critically ill patients with acute renal failure were included.…”
Section: Rationalementioning
confidence: 99%
“…Studies have demonstrated that 24%-60% of all hospitalized patients with AKI are malnourished and that ∼40% of patients are severely malnourished, as defined by the Subjective Global Assessment (SGA). [15][16][17][18] Similarly, depending on the clinical parameters used to define malnutrition, a prevalence of 31%-50% has been observed in both maintenance HD and peritoneal dialysis patients, of which 6%-8% of patients are severely malnourished. 19,20 There is evidence to suggest that malnutrition is prevalent even before initiation of RRT.…”
Section: Pew Definitionmentioning
confidence: 99%
“…Nutrition status can also affect clinical outcomes in AKI; observational studies have shown that malnutrition is associated with increased morbidity and mortality among patients with AKI and that deficits in nutrition intakes can negatively affect renal recovery. [15][16][17] Because the kidneys normally maintain acid-base, electrolyte, and fluid balance; perform gluconeogenesis; secrete erythropoietin; and activate vitamin D, the impairment of renal function requires adjustment in the provision of various macronutrients and micronutrients. 18 Additionally, the need for adequate protein administration in the setting of a catabolic condition must be weighed against the risk of azotemia in patients with AKI who have not yet started RRT.…”
Section: Nutrition Implicationsmentioning
confidence: 99%
“…As a catabolic and proinflammatory condition, AKI affects metabolism and can significantly alter nutrition status. Nutrition status can also affect clinical outcomes in AKI; observational studies have shown that malnutrition is associated with increased morbidity and mortality among patients with AKI and that deficits in nutrition intakes can negatively affect renal recovery . Because the kidneys normally maintain acid‐base, electrolyte, and fluid balance; perform gluconeogenesis; secrete erythropoietin; and activate vitamin D, the impairment of renal function requires adjustment in the provision of various macronutrients and micronutrients .…”
Section: Introductionmentioning
confidence: 99%